EPISTEMOLOGI PERSPEKTIF BARAT DAN ISLAM - Nazaruddin Butar- Butar (Program Studi Akuntansi IKOPIN, 2021)
As a religion that has a universal scientific dimension, Islam must beunderstood from all aspects without leaving the essences contained therein.Stupidity in thinking will have consequences for the crystallization of the lawso that it is unable to accommodate every event that follows. In its relevance tothe times, Islam must be able to follow the direction and goals of thesedevelopments. The existence of Islam as a religion that is rahmatan lil 'alaminmust be able to be applied in a more universal and comprehensive context.The nuanced understanding of indoctrination is gradually abandoned, so thatthe mindset of future generations of Muslims will be able to creatively buildrelevant laws without abandoning existing laws as comparative and basic materials. Knowledge must be understood as a priority need in Muslim life inthis modern era. Both the Qur'an and the hadith provide an overview of theimportance of knowledge which has implications for knowledge in human lifeboth in relation to Allah, humans and nature. Without knowledge, humans willnot get the primacy of life, both in the eyes of God and in the eyes of humans.An essential understanding of the teachings of Islam, especially those thatregulate legal matters, is a separate requirement in order to create elasticityin thinking. The existence of geographical differences and 'customs' is aninspiration for the emergence of new knowledge, especially in the context oflaw. Thus, Islam can be seen as a religion that is consistent with its originalpurpose, namely solih likuli era wa eating.